Kajian Historiografis Pada Novel “Hulubalang Raja” Karya Nur Sutan Iskandar: Historiographical Study on the Novel "Hulubalang Raja" by Nur Sutan Iskandar - Despy, Nadia Peggy (Journal of Islamic History, 2021)
He writing of the historical novel, Nur Sutan Iskandar, uses the thematic method to reveal Minangkabau Indigenous and Natural problems in various situations. In addition, Nur Sutan Iskandar also seemed not to take sides with any camp, both to the Kingdom of Inderapura, the Sultanate of Aceh and the Netherlands. From a leadership perspective, it is clear that Nur Sutan Iskandar's writings tend to refer to the Minangkabau people's Customs and Natural Traditions, namely public relations in historical writing. Research also shows that Nur Sutan Iskandar also tends to discuss the historical conflict between the Inderapura kingdom and the Aceh Darussalam kingdom. In fact, Nur Sutan Iskandar also discussed Balanda's intervention. This proves that Nur Sutan Iskandar has contributed to Indonesian historiography, even though Nur Sutan Iskandara's works are subjective because they are written in literary form.